2017
DOI: 10.1590/s0100-736x2017001100010
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and antimicrobial resistance in Escherichia coli from pig carcasses

Abstract: The increasing antimicrobial resistance observed worldwide in bacteria isolated from human and animals is a matter of extreme concern and has led to the monitoring of antimicrobial resistance in pathogenic and commensal bacteria. The aim of this study was to evaluate the antimicrobial resistance profile of Escherichia coli isolated from pig carcasses and to assess the occurrence of relevant resistance genes. A total of 319 E. coli isolates were tested for antimicrobial susceptibility against different antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(40 reference statements)
0
2
0
1
Order By: Relevance
“…All PFGE closely-related strains subjected to WGS shared several resistance genes: aadA2 (streptomycin resistance); aac(6')Iaa (amikacin and gentamicin resistance) and bla TEM-1B (ampicillin resistance). All of these genes are widely distributed in Salmonella and other enterobacteria and are usually part of MDR profiles [22,29,30,37]. Additional genes commonly reported in Salmonella, such as tetB (tetracycline resistance), sul2 (sulfonamide resistance) and floR (amphenicol resistance), were also found in most of the strains.…”
Section: Discussionmentioning
confidence: 98%
“…All PFGE closely-related strains subjected to WGS shared several resistance genes: aadA2 (streptomycin resistance); aac(6')Iaa (amikacin and gentamicin resistance) and bla TEM-1B (ampicillin resistance). All of these genes are widely distributed in Salmonella and other enterobacteria and are usually part of MDR profiles [22,29,30,37]. Additional genes commonly reported in Salmonella, such as tetB (tetracycline resistance), sul2 (sulfonamide resistance) and floR (amphenicol resistance), were also found in most of the strains.…”
Section: Discussionmentioning
confidence: 98%
“…These results contribute to the overall picture of antimicrobial resistance in E. coli in the pig industry. Studies from many countries showed that MDR- E. coli isolates from pigs were 86.2% in US (between November 2013 and December 2014) 16 , 81.1% in Vietnam (from July to September 2019) 21 , 47% in Uganda 22 , 57.3% in Indonesia (between March 2017 and February 2018) 23 , 72.5% in Brazil 24 , and 81% in China 25 . In Spain, colistin-resistant E. coli isolates from pig farms were 91.6% resistant to at least three different antimicrobial classes 8 ; in addition, 100% of mcr -positive E .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, studies on the presence of ESBL in domestic animals and free-living birds are still more scarce and were mainly concentrated in the southern and southeastern regions [41][42][43][44][45][46][47][48], with only a few studies conducted in the northeast [17,49,50]. The prevalence of ESBL-producing bacteria observed in these studies is considered variable due to the lack of a pattern in the number of samples, varying, for example, from 32 to 257 samples [50,51].…”
Section: Discussionmentioning
confidence: 99%